A classroom‐ready activity on educational disparities in the United States. (25th June 2021) - Wilson, Melody; Ross, Andrew; Casey, Stephanie
Abstract: We present a classroom‐ready activity for high school or college students involving an investigation of a rich, multivariate data set concerning educational and demographic characteristics of K‐12 schools at the state level in the United States. The data set includes educational characteristics such as per‐pupil revenue and graduation rate along with demographic characteristics such as poverty rate and economic segregation. Analysis of the data set sparks conversations regarding educational disparities for students in the United States and could prompt curiosity about educational disparities in other locations as well.